Bioclimatic coefficients of seedlings of fruit and berry crops under drip irrigation in the conditions of the Central Non-Black Earth Region - N. N. Dubenok; A. V. Gemonov; A. V. Lebedev (Овощи России, 2024)
Relevanse. An important condition for the effectiveness of gardening is the systematic replacement of old plantings with new ones. The supply of planting material to the industry is important. Imported planting material does not always meet quality requirements and is not always adapted to the soil and climatic conditions of the region in which fruit and berry plantings are planted. Despite the spread of low-volume irrigation, for the regions of the Central Non-Black Earth Region (Central NonChernozem region) of Russia, only a few studies have been carried out to study drip irrigation regimes for fruit and berry nurseries, therefore, issues related to the development of rational irrigation regimes are of particular relevance.Methods. Field research was carried out on the territory of the educational and experimental farm of the Michurinsky Garden fruit growing laboratory of the Russian State Agrarian University Moscow Timiryazev Agricultural Academy from 2011 to 2022. Field experiments on growing one-year-old, twoyear-old and three-year-old seedlings were carried out in triplicate according to the following options: 1) control (without irrigation), 2) maintaining the moisture content of the root layer in the range of 60-80 %, 3) 70-90% and 4) 80-100% of the lowest moisture capacity. The obtained experimental data were processed using regression analysis methods.Results. The resulting mathematical and statistical models make it possible to calculate the bioclimatic coefficients of plum, cherry, raspberry, pear and apple seedlings depending on pre-irrigation soil moisture and the sum of average daily temperatures for the conditions of the Central NonChernozem Zone of Russia. All the fruit and berry crops under consideration are characterized by a general pattern that, depending on the sum of average daily temperatures, bioclimatic coefficients change according to a parabolic dependence, and have minimum values at the beginning of the growing season, reach maximum values during the period of intensive growth of seedlings and gradually decrease towards the end of the growing season.